Între mâncare și hrană spirituală. Considerații asupra Jurnalului lui Paul de Alep - Florentina Nicolae (Revista de Istorie și Teorie Literară)
In this paper will shall analyse Paul of Aleppo’s Diary, regarding the food culture and its changes within the Romanian urban society in the XVIIth century. Even though the local food seems simple and plane to the writer, he appreciates its freshness and the hospitality of the officials. In the same time, his Diary offers important details regarding the trade and the circulation of the exotic food in the Romanian Principalities and changes in the food taste and eating habits of the upper class.